Feasibility and acceptability of a remotely delivered transdiagnostic CBT treatment for postnatal anxiety and related disorders: A pilot case series - Peta N Maguire; Navjot Bhullar; Suzanne M Cosh; Bethany M Wootton (Women's Health, 2023)
Women in the postnatal period are at a high risk of developing clinically significant symptoms of anxiety. Cognitive behavioural therapy is effective in the treatment of postnatal anxiety; however, there are many barriers to accessing this treatment. This study examined the feasibility and acceptability of transdiagnostic cognitive behavioural therapy delivered remotely via Internet videoconferencing. Three women ( M age  = 28.33 years; SD  = 4.04) with a postnatal anxiety-related disorder were treated using the videoconference-delivered cognitive behavioural therapy. The treatment was delivered once per week over a 5-week period. All participants met criteria for clinically significant change in anxiety symptoms at post-treatment, and one participant met criteria for clinically significant change in depressive symptoms, which was maintained at 3-month follow-up. The intervention was also found to be acceptable by participants. The results provide preliminary feasibility evidence of the clinical utility and acceptability of remotely delivered transdiagnostic cognitive behavioural therapy as an intervention for postnatal anxiety disorders.